2004
DOI: 10.1038/sj.cr.7290202
|View full text |Cite
|
Sign up to set email alerts
|

Impaired reproduction in transgenic mice overexpressing γ-aminobutyric acid transporter I (GAT1)

Abstract: It is well documented that γ-aminobutyric acid (GABA) system existed in reproductive organs. Recent researches showed that GABA A and GABA B receptors were present in testis and sperm, and might mediate the acrosome reaction induced by GABA and progesterone. GABA transporter I (GAT1) also existed in testis and sperm, but its physiological function was unknown. In the present study, we used GAT1 overexpressing mice to explore GAT1 function in male reproductive system. We found that the expression level of GAT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…2000]. Our previous studies revealed abnormal testis morphology in adult male TG mice [Ma et al 2000;Hu et al 2004]. The present study confirmed that GABA transport protein GAT1 was present in WT testes, epididymis, and sperm.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…2000]. Our previous studies revealed abnormal testis morphology in adult male TG mice [Ma et al 2000;Hu et al 2004]. The present study confirmed that GABA transport protein GAT1 was present in WT testes, epididymis, and sperm.…”
Section: Resultssupporting
confidence: 75%
“…These findings suggested that GABA and its receptors were important components of the reproductive system. The presence of GAT1 has been confirmed in rat and mouse testes and sperm [Ma et al 2000;Hu et al 2004]. In the present study, WT mice and GAT1 overexpressing TG mice were used to confirm the existence and define the location of GAT1 in the reproductive system of male mice, including testis, epididymis, and sperm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no remarkable changes in the epididymis [15]. This can explain that the male reproduction is compromised in GAT1 transgenic mice [15,16]. In the current study, we found that GABA and GAT1 distributed differentially in mouse epididymis caput, corpus, and cauda.…”
Section: Discussionmentioning
confidence: 46%
“…Thus GABA may be a physiological regulator of sperm function. GAT1 is also observed in testes, epididymis and sperms [13][14][15][16][17][18]. The function of GAT1 has been demonstrated, showing compromised reproductive capacity in the GAT1 transgenic mice.…”
Section: Introductionmentioning
confidence: 99%